- STRATEGI PEMERINTAH DESA DALAM PENINGKATAN PARTISIPASI MASYARAKAT PADA MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA BOTTO MALLANGGA KABUPATEN ENREKANG - Anggun Putri Alyas; Ahmad Mustanir; Muhammad Rais Rahmat Razak (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2025)
This study aims to examine the strategies implemented by the Botto Mallangga Village Government to enhance community participation in the Village Development Planning Meeting (Musrenbang), as well as the factors influencing participation levels. A descriptive qualitative method was used, with data collected through observation, in-depth interviews, and documentation. Informants included village officials, hamlet heads, and community leaders. The findings reveal that strategies such as direct invitation distribution, holding meetings at night, and involving local figures as intermediaries have been fairly effective. However, obstacles such as a culture of reluctance to speak, limited understanding of Musrenbang content, and the absence of a formal evaluation system hinder optimal participation. While participation is evident in the planning and implementation stages, it remains limited in sustaining the programs. The study concludes that strengthening communication, public education, and a feedback mechanism is essential to ensure that participation is not merely symbolic, but meaningful and sustainable.